Gossypiboma can remain asym ptomatic for a long time - Pant, Padam Raj; Ghimire, Asmita; Subedi, Nilam; Pant, Samriddha Raj; Shrestha, Asmita (Grande Medical Journal, 2019)
Gossypiboma, a retained foreign body after surgery, is a rare complication. It appears years after surgery, has nonspecific symptoms, and is usually identified on imaging sequences. We present here an asymptomatic case of a 32 years old lady with a history of laparotomy done two years earlier. She was initially misdiagnosed clinically and radiologically as hydatid cyst of pelvis. During re-surgery, foreign body was detected. Postoperative period was uneventful. To prevent these types of complications, we have to follow the main principle of surgery in all procedures i.e. ensuring a proper count of surgical materials before and after surgery.